2007
DOI: 10.1213/01.ane.0000285988.35174.d9
|View full text |Cite
|
Sign up to set email alerts
|

Dark Skin Decreases the Accuracy of Pulse Oximeters at Low Oxygen Saturation: The Effects of Oximeter Probe Type and Gender

Abstract: Multivariate analysis indicated that Sao2 level, sensor type, skin color, and gender were predictive of errors in Spo2 estimates at low Sao2 levels. The data suggest that clinically important bias should be considered when monitoring patients with saturations below 80%, especially those with darkly pigmented skin; but further study is needed to confirm these observations in the relevant populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
257
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(268 citation statements)
references
References 3 publications
4
257
2
5
Order By: Relevance
“…3,4 The SpO 2 overestimation may also be dependent on location of measurement, 4,5 perfusion to the extremity where the pulse oximeter is located, and skin color. 6,7 The population of children with lower baseline oxygen saturations is growing. There are many children with cyanotic congenitalheartdisease(CCHD)undergoing and surviving palliative procedures.…”
mentioning
confidence: 99%
“…3,4 The SpO 2 overestimation may also be dependent on location of measurement, 4,5 perfusion to the extremity where the pulse oximeter is located, and skin color. 6,7 The population of children with lower baseline oxygen saturations is growing. There are many children with cyanotic congenitalheartdisease(CCHD)undergoing and surviving palliative procedures.…”
mentioning
confidence: 99%
“…It Table 1 -Descriptive measurements of oxygen saturation (%) by finger, nail polish color, and the right hand (without enamel) and the left hand (with enamel). represents a significant advance because it allows for reliable measurements of oxygen saturation, avoiding the discomfort and the risk caused by arterial punctures, as well as quickly identifying situations of hypoxia, facilitating clinical decisions (7)(8)14,17,(21)(22)(23)(24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…But factors exist that lead to inaccuracy of pulse oximetry, among these are: the situation in which the oxygen saturation is below 70%; skin pigmentation; nail polish; light in the environment, such as surgical lamps; fluorescent and fiberoptic instruments; movement of the sensor; sensor is not compatible with the device; shock state in which there is poor tissue perfusion, carboxyhemoglobin (COHb) -hemoglobin that has a higher affinity to carbon monoxide, reducing the bond to oxygen, methemoglobin (MetHb) -oxidation of ferrous ion to ferric form which impedes the hemoglobin from binding to oxygen; errors in readings due to increases in serum lipid and bilirubin levels artificially altering the levels of COHb and MetHb; lack of calibration of the device; intravascular dyes such as blue methylene, indocyanine green and indigo red and onychomycosis (7,(14)(15)(16)(17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%
“…The darker pigmentation of the Hispanic population can also have impact on pulse oximetry readings [10]. A study by Feiner et al [10] found that pulse oximeters generally overestimate blood oxygenation saturation in patients with hypoxia defined as saturations less than 80 percent.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…A study by Feiner et al [10] found that pulse oximeters generally overestimate blood oxygenation saturation in patients with hypoxia defined as saturations less than 80 percent. …”
Section: Anesthetic Considerationsmentioning
confidence: 99%